1997
DOI: 10.1097/00005537-199703000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sinus Surgery on Pulmonary Function in Patients With Cystic Fibrosis

Abstract: The impact of sinus surgery on the pulmonary status of cystic fibrosis patients is unknown. This retrospective study reviewed the charts of the cystic fibrosis patients presenting to our institution's cystic fibrosis center with nasal obstruction, recurrent sinusitis, and nasal polyposis. This group subsequently underwent endoscopic ethmoidectomy and antrostomy. Fourteen of the 15 patients, ages 5-24 years, received preoperative and postoperative pulmonary function testing obtained by spirometry. The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 13 publications
3
54
1
Order By: Relevance
“…29,30 The link between CRS and pulmonary function in the CF population is less defined. In 1997, Madonna et al 31 failed to reveal any improvement in FEV 1 % in 15 pediatric CF patients after undergoing aggressive medical and surgical management of their sinus disease. However, in 2006 Shatz did show improvement in FEV 1 % and decrease in hospital admissions after aggressive surgical management of 15 pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The link between CRS and pulmonary function in the CF population is less defined. In 1997, Madonna et al 31 failed to reveal any improvement in FEV 1 % in 15 pediatric CF patients after undergoing aggressive medical and surgical management of their sinus disease. However, in 2006 Shatz did show improvement in FEV 1 % and decrease in hospital admissions after aggressive surgical management of 15 pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…An effect of ESS on pulmonary status was initially reported in a small study among adult CF patients, which showed that pulmonary symptoms, but not function, improved after sinus surgery [55]. Madonna et al studied the effects of sinus surgery on pulmonary function in CF and did not demonstrate a significant improvement [56]. On the other hand, a larger retrospective study showed that although CF patients did not have a significant difference in pulmonary function test results or steroid requirements, they did have a reduced need for hospitalization in the 6 months following ESS [57].…”
Section: Managementmentioning
confidence: 99%
“…Such studies might provide an aid in prevention of disease recurrence and revision procedures. The lack of effect of ESS on pulmonary function test results in previous retrospective studies [55, 56, 58] highlights the need for prospective assessment of pulmonary effects, as well as postoperative quality of life improvement and of adjunct medical therapy efficacy for pulmonary symptoms.…”
Section: Future Directionsmentioning
confidence: 99%
“…Results were divergent in other studies, however. 27 In a classical study of 20 patients, Shapiro et al conducted 34 maxillary sinus needle aspirates and found bacterial growth in 76% of cases. At least one aspirated sinus was positive in 19 of the 20 patients (95%).…”
Section: Discussionmentioning
confidence: 99%